Prioritizing Chinese medicine clinical research questions in cancer palliative care from patient and caregiver perspectives - Charlene H. L. Wong; Wendy Wong; Wai Ling Lin; David K. Y. Au; Justin C. Y. Wu; Ting Hung Leung; Irene X. Y. Wu; Vincent C. H. Chung (Wiley, 2021)
Abstract Background Chinese medicine (CM) modalities, including acupuncture and Chinese herbal medicine (CHM), are popular palliative interventions among patients with cancer, but further clinical research is required to assess their effectiveness and safety. Objective To prioritize top ten important CM clinical research questions from patients with cancer, cancer survivors and caregivers' perspectives via a face‐to‐face prioritization workshop in Hong Kong. Methods A list of 25 CM clinical research questions for cancer palliative care, which were identified from existing systematic reviews (SRs) and overview of SRs, was presented to 17 participants (patients with cancer [n = 5], cancer survivors [n = 6] and caregivers [n = 6]). The participants were then invited to establish consensus on prioritizing top ten research questions. Results Among the top ten priorities, five (50%) focused on acupuncture and related therapies, while five (50%) were on CHM. The three most important research priorities were (i) manual acupuncture plus opioids for relieving pain; (ii) CHM for improving quality of life among patients receiving chemotherapy; and (iii) concurrent use of CHM plus loperamide for reducing stomatitis. Conclusion The top ten participant‐endorsed CM clinical research priorities for cancer palliative care can guide local researchers on future direction. They can also inform local research funders on patient‐centred allocation of limited funding. Under limited research funding, the most important co‐prioritized research question from professional and patient perspectives may be addressed first. Patient or Public Contribution Patients with cancer, cancer survivors and caregivers participated in conduct of the study to prioritize CM clinical research questions.